Difficulties in Field Study of Education Students - Santiago, Lilia M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to identify the challenges faced by Education students during their Field Study (FS) courses in the second semester of the 2016-2017 academic year. Focusing on three specific FS courses—Field Study 2: “Experiencing the Teaching-Learning Process,” Field Study 5: “Learning Assessment Strategies,” and Field Study 6: “On Becoming a Teacher”—the research utilized a descriptive survey method, incorporating documentary analysis of grading sheets and workbooks. The findings highlighted three primary issues contributing to the difficulties experienced by students: challenges with resource teachers, learner behavior, and self-related issues among the FS students. To address these challenges, participants proposed several solutions, leading to the recommendation that both the Teacher Education Institution (TEI) and the Department of Education (DepEd) revisit their Memorandum of Agreement (MOA) prior to the commencement of Field Study courses, ideally through a formal ceremony.